Reckonings with the past: a cultural geography of (re)narrating women's histories through popular culture - Shackman, Leah (2019)
Pivoting on the creation of a feminist revisionist history, this project establishes a cultural geography of the narration or re-narration of the histories, lives and achievements of female historical figures through different forms of popular culture. To achieve this, this project explores the We Are Bess photography exhibition, the children’s non-fiction book Good Night Stories for Rebel Girls, and the film Hidden Figures. Focusing its attention on the present-day engagement with history, this project explores the successes, complexities and critiques of creating a feminist revisionist history; illustrates how individual histories can be used to discuss broader theoretical ideas in feminist geography; and reveals the interconnected nature of women’s experiences past and present.